Estratégias bioclimáticas para seis cidades alagoanas: contribuições para a adequação da arquitetura ao clima local - Silva, Mônica Ferreira da (2019)
Knowledge of the climatic profile of a locality is essential to support the formulation of project recommendations that seek the adaptation of buildings to local climatic conditions through bioclimatology. This study summarizes bioclimatic strategies recommended for architectural planning in six cities in Alagoas, with a view to obtaining thermal comfort and energy efficiency in the inhabited space. The methodological procedures adopted in this research consisted of four stages: definition of the cities to be studied; obtaining, treating and analyzing the raw climate data of each city; determination of bioclimatic strategies based on the Givoni Bioclimatic Chart and the Fuzzy Mahoney’s Method; and, finally, synthesis of the project recommendations for the cities under study. The selection of the cities to be analyzed considered their location, as well as the availability of their hourly climate data, being chosen the cities of Arapiraca, Coruripe, Maceió, Palmeira dos Índios, Pão de Açúcar and São Luís do Quitunde. The climatic information of the cities corresponded to hourly climatic data collected by automatic meteorological stations of the National Institute of Meteorology installed in the respective municipalities for the period from 2009 to 2018. The treatment of the data consisted of three stages: verification of the consistency of the data, obtaining indicators of climate description and determination of the Test Reference Year of each location. The examination of the data revealed that the quantities of gaps vary greatly between the cities, with precipitation being the variable that suffers most from the lack of data. The analysis of climate indicators highlighted the similarities and particularities of climate between cities. The Test Reference Years and the average data from the cities underpinned the project recommendations obtained through the Givoni Chart and the Fuzzy Mahoney’s Method, respectively. The main differences in the bioclimatic strategies indicated for the cities were related to the size and position of the openings, the spacing between the buildings and the need for protection against intense rainfall. The use of high thermal inertia in walls is the strategy that requires more attention due to the lack of definition of the methodologies. It was concluded that there is a need for improvement of the Fuzzy Mahoney’s Method in relation to Table III. Finally, this paper assists designers in choosing bioclimatic strategies suitable for architectural planning in the six cities studied in Alagoas